2021
DOI: 10.1111/ctr.14375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐intensity training on bone health and body composition in lung transplant recipients: A secondary analysis of a randomized controlled trial

Abstract: Lung transplantation (LTx) is a life-saving treatment for patients with terminal lung disease. Although LTx prolongs survival and improves quality of life in appropriately selected patients, it is also associated with morbidities that may complicate long-term outcomes, among them osteoporosis and sarcopenia. 1,2 A high prevalence of osteoporosis has been reported following solid organ transplantation, and LTx recipients seem to be the most susceptible. 3,4 Studies have shown a bone mineral density (BMD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This shows that the patients in the observation group who did the physical rehabilitation training had significantly improved postoperative functions, and the rehabilitation effect was very good. This is consistent with the research results of Ulvestad et al (26). In addition, 75% of patients in the observation group were satisfied with rehabilitation nursing, which was significantly better than the 54.17% of the control group, and the difference was statistically significant (P<0.05).…”
Section: Early Physical Training Can Improve Lung Function and Motor ...supporting
confidence: 92%
“…This shows that the patients in the observation group who did the physical rehabilitation training had significantly improved postoperative functions, and the rehabilitation effect was very good. This is consistent with the research results of Ulvestad et al (26). In addition, 75% of patients in the observation group were satisfied with rehabilitation nursing, which was significantly better than the 54.17% of the control group, and the difference was statistically significant (P<0.05).…”
Section: Early Physical Training Can Improve Lung Function and Motor ...supporting
confidence: 92%
“…Although we observed an increase in lumbar spine TBS over the off-season period, this change was not affected by the intervention. This contrasts with previous work showing a positive effect on lumbar spine TBS following 20 weeks of resistancetype exercise training, albeit in older adults (Pinho et al, 2020;Ulvestad et al, 2021). It is worth noting that those studies included specific resistance exercises that load the lower back (i.e., squats, back extensions).…”
Section: Discussionmentioning
confidence: 74%
“…Exercise training can be successful in reversing these consequences. For example, a recent study showed improved bone health after exercise training in patients after lung transplantation [ 112 ] and another study showed promising results in terms of improved blood pressure [ 113 ].…”
Section: Scenarios For Pulmonary Rehabilitation In Patients With Copdmentioning
confidence: 99%